Study of Jetty Planning as Coastal Protection Structure to Address Estuary Sedimentation: Case Study of Lubuk Tukko Beach, North Sumatra Province - M Gilang Indra Mardika; Indri Rahmandhani Fitriana; Tera Melya Patrice Sihombing; Oscar Lumbantobing (Universitas Sulawesi Barat, 2025)
Sediment transport from the sea can cause estuary siltation. The effective jetty construction planning is one of problem addressing structurely. To derive the elevation and dimensions of an effective jetty structure in addressing the estuary sedimentation at Lubuk Tukko Beach, North Sumatra Province, wave analysis is conducted using the hindcasting method and tidal analysis using the admiralty method. The research analysis show that the wave height design is 0.676 meters and the highest water surface elevation is 0.616 meters. The type of jetty used is a long jetty with a left jetty length of 394 meters and a right jetty length of 426 meters. The elevation of the right jetty end is 2.5 meters, with a building top width of 1 meter, and the elevation of the left jetty end is 2.6 meters, with a top width structure of 1 meter.